O massacre do Caldeirão da Santa Cruz do Deserto: uma análise da legitimação da violência e autoritarismo para o rompimento de garantias fundamentais - Silvestre, Mauro Wesllen Tavares (2023)
The objective of this research is to analyze the multiple narratives that justify the adoption of authoritarian measures, which result in violence towards vulnerable categories, violating guarantees of constitutional orders. To understand this proposal, the massacre of the Messianic community of Caldeirão da Santa Cruz do Deserto, existing in Cariri Ceará in the first half of the 20th century, is used as an object of analysis. Considering the multiple discourses enunciated by different actors and institutions regarding that category of individuals, and analyzing based on the association of such facts, with appropriate theoretical currents that seek to find answers to the question, which involves the perspective of power as an instrument generating impact on people, as well as Law being used to protect individual interests over collective ones, enunciating its political position that breaks with traditional dogmatics. These perspectives are examined based on the historical evolution of the identity of the people of Cariri, considering different events that mark the 19th and 20th centuries, as well as the journey of constitutional thought. In this way, the relevance of the work is based on the perception that such issues impact today's Cariri, guiding the region's identity. Throughout the proposal presented in the work, the interdisciplinarity between philosophy, sociology, psychology and law is considered, which at different moments are related in events, analyzing the past of the constitution and the transmission of the authoritarian and violent pattern. Therefore, it was realized throughout the research that the problems in Cariri today, especially in the issue of violence, are the results of historical processes, which, as pointed out, are denied and/or made invisible. The exposure of the problem is what allows its resolution, therefore, the necessary revisiting of these phenomena from a critical perspective is proposed, in order to mobilize society to engage in the construction of means to resolve the issue, as suggested by the perspective of the Critical Theory of Law on emancipatory logic.